IMPLEMENTASI SUPERVISI KUNJUNGAN KELAS KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SDN KROOY KABUPATEN KAIMANA PAPUA BARAT - Amatus Mikhael Rumlus; Yulius Mataputun; Indah Slamet Budiarti (Vidya Karya, 2021)
This study aimed to analyze the implementation of classroom visit supervision to improve teacher performance at SD Negeri Krooy, Kaimana Regency, West Papua Province. This research is qualitative research using the descriptive method. The informants are the principal, teacher supervisor. To obtain data, in-depth interviews, participatory observations, and documentation studies were conducted. The research instrument used was an observation interview guide and a documentation checklist. The results of this study are: 1) The principal prepares the program, and determines the schedule for the implementation of supervision through class visits by informing, the principal prepares administration, and prepares mastery materials; 2) Supervision of class visits without prior notification, supervisors suddenly come to class and check the lesson plans, and syllabus; 3) Implementation of class visit supervision at the invitation of the teacher, the principal fulfills the invitation of the teacher supervision teacher by checking the lesson plans, and syllabus; 4) Implementation of the supervision of the principal's class visits to overcome the obstacles of lack of confidence, lack of scientific spirit, weak creativity, and lack of facilities; and 5) The impact can improve the quality of teacher performance, increase the effectiveness of the curriculum, increase the effectiveness and efficiency of facilities and infrastructure, improve the quality of school management.Keywords: Classroom Visit Supervision; Principal; Teacher PerformanceTujuan dari penelitian ini adalah menganalisis pelaksanaan supervisi kunjungan kelas dalam rangka meningkatkan kinerja guru di SD Negeri Krooy Kabupaten Kaimana, Provinsi Papua Barat. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode deskriptif. Informannya adalah kepala sekolah, pengawas guru. Untuk memperoleh data dilakukan wawancara mendalam, observasi partisipatif, dan studi dokumentasi. Instrumen penelitian yang digunakan ialah pedoman wawancara observasi dan checklist dokumentasi. Hasil dari penelitian ini adalah: 1) Kepala sekolah menyusun program, dan menentukan jadwal pelaksanaan supervisi melalui kunjungan kelas dengan memberitahukan, kepala sekolah menyiapkan administrasi, dan menyusun materi penguasaan; 2) Pelaksanaan supervisi kunjungan kelas tanpa adanya pemberitahuan awal, pengawas tiba-tiba datang ke kelas dan mengecek RPP, dan silabus; 3) Pelaksanaan supervisi kunjungan kelas atas undangan guru, kepala sekolah memenuhi undangan guru supervisi guru dengan memeriksa RPP, dan silabus; 4) Pelaksanaan supervisi kunjungan kelas kepala sekolah mengatasi kendala kurang percaya diri, kurang semangat keilmuan, lemah kreativitas, dan minim fasilitas; dan 5) Dampaknya dapat meningkatkan kualitas kinerja guru, meningkatkan efektivitas kurikulum, meningkatkan efektivitas dan efisiensi sarana dan prasarana, meningkatkan kualitas manajemen sekolah.Kata Kunci: Supervisi Kunjungan Kelas; Kepala Sekolah; Kinerja Guru